2020
DOI: 10.5435/jaaos-d-19-00041
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Warming Reduces Intraoperative Hypothermia in Total Joint Arthroplasty Patients

Abstract: Introduction: Perioperative hypothermia (PH) is common in patients undergoing total joint arthroplasty (TJA). A previous study at our institution identified the largest drop in core body temperature between preoperative holding and induction of anesthesia. This study evaluates the effect of preoperative warming measures on PH in TJA patients. Methods: A retrospective review was conducted of 672 patients undergoing TJA at our institution between April 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Thus, our study suggests the importance of intraoperative hypothermia management and preventive measures. In addition, some researchers recommend active skin warming and heating, timely blood transfusion in patients with excessive blood loss, prophylactic platelet transfusion in patients with low preoperative PLT count to reduce the incidence of hypothermia (Kay et al, 2020b; Liu et al, 2019; Nordgren et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our study suggests the importance of intraoperative hypothermia management and preventive measures. In addition, some researchers recommend active skin warming and heating, timely blood transfusion in patients with excessive blood loss, prophylactic platelet transfusion in patients with low preoperative PLT count to reduce the incidence of hypothermia (Kay et al, 2020b; Liu et al, 2019; Nordgren et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, increasingly, medical staff pay attention to the study of perioperative hypothermia, which has gradually become a challenge for postoperative management. Previous studies reported that the risk factors affecting intraoperative hypothermia in patients with joint replacement were complex and changeable, which could be mainly summarised as follows:(1) Patients' factors: elderly women, low BMI and low basal body temperature were high-risk factors for hypothermia (Frisch et al, 2017;Jildeh et al, 2018a;Pu et al, 2022a;; (2) Heat preservation measures: active heat preservation (external heat applied to skin and surrounding tissues, such as forced air heating) could reduce the risk of hypothermia by 29%, when compared with passive heat preservation (helping heat storage and preventing loss, such as blanketing) and the combined application of multiple active heat preservation measures could significantly reduce the incidence of hypothermia (Jun et al, 2019;Kay et al, 2020a;Nordgren et al, 2020a); (3) Anaesthesia duration: for every 1 min increase in anaesthesia duration, the core body temperature of patients decreased by .00298°C (Emmert et al, 2018);…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Body temperature has been reported to drop obviously between preoperative holding and induction of anesthesia [12]. A previous study used preoperative forced-air warming and found that it could significantly decrease the rate of intraoperative hypothermia [24].…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…46,47 However, based on this review of the current literature, the most effective and efficient method of warming is via forced warm air, 42,48 which ideally should begin preoperatively because there can be a large temperature drop between preoperative holding and induction of anesthesia. 42,44 To prevent this drop, a recent study by Kay et al 49 found that forced-air gowns in the preoperative holding area reduced perioperative hypothermia by 30%. Current literature continues to support the maintenance of normothermia perioperatively, with forced-air methods proving the most effective.…”
Section: Temperaturementioning
confidence: 99%